Prognostic value of colour Doppler brain sonography for the neurodevelopmental outcome in term neonates with hypoxic ischaemic encephalopathy - Emina Hadžimuratović; Suada Branković; Admir Hadžimuratović; Melika Bukvić (Medicinski glasnik, 2022)
Aim: To determine a prognostic value of cerebral blood flow parameters for the development of neurological sequelae in term neonates with hypoxic ischaemic encephalopathy (HIE). Methods: We reviewed medical records of 47 term neonates with HIE who survived until the age of 12 months of life. According to the Sarnat and Sarnat clinical score, neonates were divided into 3 groups: mild HIE, moderate HIE and severe HIE. All included neonates had the colour Doppler brain sonography performed in the first 24 hours of life. The neurological assessment was done at the age of 12 months of life by using the Denver Developmental Screening Test (DDST). Logic regression analysis was performed using the colour doppler brain sonography parameters with the development of neurological impairment as the primary outcome. Results: Out of 47 neonates, 19 (40.4%) were with mild, 17 (36.2%) with moderate and 11 (23.4%) with severe HIE. The values of cerebral blood flow parameters and resistance index (RI) significantly correlated with the neurological impairment at the age of 12 months of life (p<0.001). The limit value of RI indicating the poor neurodevelopmental outcome was 0.81, sensitivity 80%, specificity 85.3%, positive predictive value 52.2% and negative predictive value 95.2%. Conclusion: The cerebral blood flow parameters measured with colour doppler brain sonography are good indicators of the severity of HIE and later neurodevelopmetal outcome.
Keywords: asphyxia neonatorum; cerebral blood flow; neurodevelopmental disorders